Effect of Improperly Sized Shoes on Gait (Journal of Fiber Bioengineering and Informatics, 2014)
Although shoes are conventionally chosen based on the size indicated on the label, it is also possible toaccurately gauge foot size using a technique known as morphometry to measure the three-dimensionalshape of feet in a state of rest. However, because shoe sizes differ slightly for each shoe manufacturerdespite the use of a standardized labeling system, there is no guarantee that consumers will be able tochoose a pair of shoes that properly fit the size of their feet. Furthermore, some consumers are in thehabit of wearing larger shoes to accommodate the width of their feet. The purpose of this study wasto develop a quantitative understanding of the relationship between shoe size (foot length) and gait byusing techniques such as electromyogram of the lower leg, measurement of ground reaction force, andsubjective evaluation.The subjects, five male university students with no history of leg injury, all had a foot length of 26.5cm and a foot width of size D as defined by JIS standards. Prior to the experiment, the subjects' consentwere obtained after briefing them on anticipated risks and safety considerations, management of theirpersonal information, and other aspects of the study. Experimental samples consisted of a total of fiveD-width shoes in sizes ranging from 26.0 cm to 28.0 cm, in 0.5 cm increments. Each subject was fittedwith an electromyogram measuring device on the gastrocnemius and tibialis anterior muscles on his rightleg, and a plantar pressure distribution measuring sheet was placed in each of the sample shoes. Eachsubject took 10 strides while wearing each sample shoe along a predetermined route in the lab, underwhich a device for measuring floor reaction force had been installed. After each subject had walked ineach shoe sample, they filled out a questionnaire on the sensations experienced while walking. Whenthe shoe size (foot length) was at least 1 cm longer than the subject's proper size, a significant increasein activity by the gastrocnemius muscle was noted along with a significant decrease in the floor reactionforce value (F2) at kick-off. These changes were attributed to the psychological effects of factors suchas ease of kick-off. The findings suggest that the parameters used in this study, including muscularactivity level, floor reaction force peak value, and gait reproducibility, have the potential to serve asuseful indicators in evaluating the functional compatibility between shoe wearers and shoe size.
Keywords: Shoe Size (Foot Length); Gait; Lower Leg; Ground Reaction Force; Subjective Evaluation; Gastrocnemius; Tibialis Anterior